SURFACE TREATMENT AGENT FOR ORGANIC-INORGANIC HYBRID COMPOSITION
A surface treatment agent for inorganic hybrid compositions addresses refractive index differences in optical transparent adhesives, enhancing compatibility and optical properties to produce a transparent adhesive film with improved mechanical strength.
Patent Information
- Application Number
- JP2022199392
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-12-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-14
AI Technical Summary
Conventional optical transparent adhesives used in touch panels face issues due to refractive index differences between organic and inorganic layers, leading to compatibility problems and optical characteristics degradation.
A surface treatment agent for inorganic hybrid compositions, containing specific compounds and polymerization agents, is applied to inorganic particles to enhance compatibility and optical properties, forming an optically transparent adhesive film.
The solution provides an optically transparent adhesive film with improved refractive index, reduced haze, and enhanced mechanical strength, suitable for applications in touch panels.
Smart Images

Figure 0007623339000001 
Figure 0007623339000002 
Figure 0007623339000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface treatment agent for an organic-inorganic hybrid composition. [Background technology]
[0002] Optically clear adhesive (OCA) film is a transparent adhesive film used to bond optical components. In recent years, the demand for touch panels has been rapidly increasing in the fields of smartphones, tablet PCs, portable game consoles, and car navigation devices, and the demand for OCA film, which is used to bond touch panels to other optical components, has also been rapidly increasing.
[0003] A display device with a touch panel usually has a laminated structure of optical components such as a display panel such as a liquid crystal panel, a touch panel body with a transparent conductive film made of indium tin oxide (ITO) on the surface, and a cover panel to protect the transparent conductive film, and an optical transparent adhesive can be used in the form of a film to bond the optical components. As the demand for OCA film increases, interest in the adhesive materials used in it is also increasing.
[0004] Conventional optically transparent adhesives include those made from organic materials such as silicone-based resins, polyurethane-based resins, and olefin-based resins. However, when such organic-based optically transparent adhesives are used in display optical materials, problems can arise that affect the optical properties due to the difference in refractive index between the laminated layers.
[0005] To address this issue, a technology has been developed to increase the refractive index by mixing inorganic particles into an organic-based optically transparent adhesive. However, compatibility can be an issue when mixing organic and inorganic particles.
[0006] The above-mentioned background art is owned or acquired by the inventors in the process of arriving at the contents of the disclosure of this application, and is not necessarily publicly known art that was disclosed to the general public prior to the filing of this application. Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above problems, the present invention provides a surface treatment agent for an organic-inorganic hybrid composition.
[0008] According to one embodiment of the present invention, an organic-inorganic hybrid composition is provided.
[0009] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by a person having ordinary skill in the relevant technical field from the following description. [Means for solving the problem]
[0010] The surface treatment agent for an organic-inorganic hybrid composition according to one embodiment of the present invention may contain a compound represented by any one of the following [Chemical Formula 1] to [Chemical Formula 3].
[0011] [ka]
[0012] (The above R1 to R3 are each H, a saturated or unsaturated straight or branched C1-C 20 and R4 includes at least one of an alkyl group, a hydroxyl group, a silane group, and an alkoxysilane group, and R4 includes H or a hydroxyl group.
[0013] According to one embodiment, R1 to R3 are each C2-C 12 Alkyltrimethoxysilane groups, C2-C 12 Alkyltriethoxysilane groups, and C2-C 12The silane group may contain at least one selected from the group consisting of alkyldimethoxyethoxysilane groups.
[0014] According to one embodiment, R4 may include at least one selected from the group consisting of H, a 2-hydroxyethyl group, a 3-hydroxypropyl group, and a 2-hydroxybutyl group.
[0015] According to one embodiment, m and n may have an integer ratio between 1:2 and 2:1.
[0016] According to an embodiment, the surface treatment agent may further include a polymerization initiator including at least one selected from the group consisting of BPO, AIBN, and AIBA.
[0017] According to one embodiment, the polymerization initiator may be present in an amount of 0.1% by weight to 1% by weight in the surface treatment agent.
[0018] According to an embodiment, the light transmittance of the surface treatment agent may be 40% or more.
[0019] According to one embodiment, the haze of the surface treatment agent may be less than 80%. Effect of the Invention
[0020] The present invention can provide a surface treatment agent for an organic-inorganic hybrid composition.
[0021] According to one embodiment of the present invention, an organic-inorganic hybrid composition can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The embodiments are described in detail below with reference to the following. However, since various modifications can be made to the embodiments, the scope of the patent application is not limited or restricted by these embodiments. It should be understood that all modifications, equivalents, or alternatives to the embodiments are included in the scope of the patent.
[0023] The terms used in the examples are merely used for the purpose of explanation and should not be construed as limiting. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described herein, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0024] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which the embodiments belong. Terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with the contextual meaning of the relevant art, and should not be interpreted as idealized or overly formal unless expressly defined in this application.
[0025] In addition, terms such as first, second, A, B, (a), (b), etc. may be used to describe components of the embodiments. Such terms are merely intended to distinguish the components from other components, and do not limit the nature, order, or sequence of the components. When a component is described as being "coupled," "coupled," or "connected" to another component, it should be understood that the component may be directly coupled or connected to the other component, but other components may also be "coupled," "coupled," or "connected" between each component.
[0026] Components included in any of the embodiments and components having common functions will be described using the same names in other embodiments. Unless otherwise specified, the description of any of the embodiments may be applied to other embodiments, and detailed description will be omitted to the extent that they overlap.
[0027] The organic-inorganic hybrid composition according to an embodiment of the present invention may include inorganic particles surface-modified by a surface treatment agent and an acrylic monomer. According to an embodiment, the organic-inorganic hybrid composition may be cured to form an adhesive film, and according to the present invention, the organic-inorganic hybrid composition may provide an inorganic particle dispersion composition that is optically transparent or substantially optically transparent.
[0028] According to one embodiment, the surface of the inorganic particles can be modified using a surface treatment agent to improve the dispersibility of the inorganic particles, and the inorganic particles can be uniformly dispersed in the composition to provide an optically transparent inorganic particle dispersion composition.
[0029] According to an embodiment, the surface-modified inorganic particles and the acrylic monomer may have a weight ratio of 1: 1 to 2: 1. According to an embodiment, it is preferable that the weight of the acrylic monomer is equal to or greater than the weight of the surface-modified inorganic particles.
[0030] According to an embodiment, the inorganic particles may be metal oxides. According to an embodiment, the inorganic particles may be metal oxides and may be included in a transparent polymer resin to increase the refractive index.
[0031] According to one embodiment, the inorganic particles are ZrO2, SiO2, Al2O3, CeO2, ZnO, V2O5TiO2, BaTiO3, SrTiO3, BaTiO3, PbTiO3, PbZrO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), (1-x)Pb(Mg 1 / 3 Nb 2 / 3)O3-xPbTiO3(PMN-PT), HfO2, and BN.
[0032] According to an embodiment, the inorganic particles may preferably include zirconia (ZrO2). Zirconia is transparent, has a high Abbe number, and has excellent mechanical strength and thermal stability, and may be suitable for the composition according to an embodiment of the present invention.
[0033] According to an embodiment, the inorganic particles may be nano-inorganic particles. According to an embodiment, the diameter of the inorganic particles may be 10 nm to 200 nm. In this case, the diameter of the inorganic particles may mean the average diameter of the inorganic particles. In addition, the diameter of the inorganic particles may mean the diameter of the inorganic particles that are not surface-modified with a surface treatment agent.
[0034] According to one embodiment, the diameter of the inorganic particles may be 10 nm or more, 20 nm or more, 30 nm or more, 40 nm or more, 50 nm or more, 60 nm or more, 70 nm or more, 80 nm or more, 90 nm or more, 100 nm or more, 110 nm or more, 120 nm or more, 130 nm or more, 140 nm or more, 150 nm or more, 160 nm or more, 170 nm or more, 180 nm or more, or 190 nm or more, or 200 nm or less, 190 nm or less, 180 nm or less, 170 nm or less, 160 nm or less, 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, or 60 nm or less, or may be included in a range between two values selected from the above mentioned numerical values.
[0035] According to one embodiment, if the diameter of the inorganic particles is less than 10 nm, dispersion may be difficult due to increased surface energy of the inorganic particles, and if the diameter exceeds 200 nm, a scattering effect may occur, reducing the visibility of the adhesive film and increasing the thickness of the adhesive film.
[0036] According to one embodiment, the specific surface area of the inorganic particles is 1 m 2 / g~250m 2 / g. In this case, the specific surface area of the inorganic particles may mean the average of the specific surface areas of the inorganic particles. The specific surface area of the inorganic particles may be measured by measuring the specific surface area of inorganic particles that have not been surface-modified with a surface treatment agent.
[0037] According to one embodiment, the specific surface area of the inorganic particles is 1 m 2 / g or more, 10m 2 / g or more, 30m 2 / g or more, 50m 2 / g or more, 70m 2 / g or more, 90m 2 / g or more, 110m 2 / g or more, 130m 2 / g or more, 150m 2 / g or more, 170m 2 / g or more, 190m 2 / g or more, 210m 2 / g or more, or 230m 2 / g or more or 250m 2 / g or less, 230m 2 / g or less, 210m 2 / g or less, 190m 2 / g or less, 170m 2 / g or less, 150m 2 / g or less, 130m 2 / g or less, 110m 2 / g or less, 90m 2 / g or less, or 70m 2 / g or less or may be in a range between any two values selected from those mentioned above.
[0038] According to an embodiment, when the specific surface area of the inorganic particles is outside the above range, the transmittance may decrease, quality may be deteriorated due to scattering, and agglomeration may occur.
[0039] According to one embodiment, the surface-modified inorganic particles may be present in an amount of 40% to 50% by weight of the composition. According to one embodiment, the surface-modified inorganic particles may be present in an amount of 40% to 45% by weight, or 45% to 50% by weight of the composition.
[0040] According to one embodiment, if the surface-modified inorganic particles in the composition are less than 40 wt%, the relative proportion of the inorganic particles in the composition is low, and the refractive index and brightness of the composition may decrease, and if the proportion exceeds 50 wt%, a cloudy phenomenon may occur during subsequent production of the adhesive film. According to one embodiment, the acrylic monomer may include at least one selected from the group consisting of butyl acrylate, 2-ethylhexyl acrylate, isobornyl acrylate, and 4-acryloyl morpholine.
[0041] The composition according to an embodiment of the present invention can be cured to produce an adhesive film. By using an acrylic monomer, an adhesive film that is flexible and has excellent optical properties can be produced.
[0042] According to an embodiment, the acrylic monomer may be 50% to 60% by weight of the composition. According to an embodiment, the acrylic monomer may be 50% to 55% by weight, or 55% to 60% by weight.
[0043] According to one embodiment, if the acrylic monomer is less than 50 wt % in the composition, the proportion of inorganic particles will be high and the viscosity may increase, and if it exceeds 60 wt %, the proportion of inorganic particles will be low, the refractive index and brightness of the adhesive film will decrease, and cloudiness may occur.
[0044] According to an embodiment, the surface treatment agent may be a copolymer of a silane-based monomer and a methacrylate-based monomer. Specifically, the surface treatment agent may be a random copolymer of a silane-based monomer and a methacrylate-based monomer.
[0045] According to one embodiment, the silane-based monomer is silane, C1-C 20 The silane may include at least one selected from the group consisting of alkylsilane, alkoxysilane, isocyanate silane, aminosilane, epoxysilane, acrylsilane, mercaptosilane, fluorine silane, methacryloxy silane, vinylsilane, phenylsilane, chlorosilane, and silazane.
[0046] According to an embodiment, the silane-based monomer is specifically a vinyl group-containing silane-based monomer including at least one selected from the group consisting of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltris(2-methoxyethoxy)silane; a methacryloxy group-containing silane-based monomer including at least one selected from the group consisting of 3-methacryloxypropyltrimethoxysilane (MPTMS), 3-methacryloxypropyltriethoxysilane (MPTES), 3-methacryloxypropylmethyldimethoxysilane, and 3-methacryloxypropylmethyldiethoxysilane. silane monomers containing acetoxy groups, including vinyltriacetoxysilane; 3-acryloxypropyltrimethoxysilane (APTMS), 3-acryloxypropyltriethoxysilane, or both; 3-glycidoxypropyltrimethoxysilane (GPTMS), 3-glycidoxypropyltriethoxysilane (GPTES), 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane), an epoxy group-containing silane monomer containing at least one selected from the group consisting of vinyltrichlorosilane, a chloro group-containing silane monomer containing vinyltrichlorosilane, a mercapto group-containing silane monomer containing at least one selected from the group consisting of 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane, 3-trimethoxysilylpropyl succinic anhydride, 3-triethoxysilylpropyl succinic anhydride, 3-triethoxysilylpropyl succinic anhydride, anhydride-containing silane monomers, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-2-(aminoethyl)-3-aminopropyltrimethoxysilane-containing amino group-containing silane monomers, and 3-isocyanatopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, or at least one selected from the group consisting of both isocyanate group-containing silane monomers. According to one embodiment, the silane monomer may be a silane coupling agent.
[0047] According to an embodiment, the methacrylate monomer may include at least one selected from the group consisting of 2-hydroxyethyl methacrylate (2-HEMA), 2-hydroxypropyl methacrylate (2-HPMA), and 2-hydroxy-1-methylethyl methacrylate.
[0048] According to one embodiment, the surface treatment agent may contain a compound represented by any one of the following [Chemical Formula 1] to [Chemical Formula 3].
[0049] [ka]
[0050] In this case, R1 to R3 are each H, a saturated or unsaturated straight or branched chain C1-C 20 wherein R4 contains at least one of an alkyl group, a hydroxyl group, a silane group, and an alkoxysilane group, and R4 may contain H or a hydroxyl group.
[0051] According to one embodiment, for example, R1 to R3 are each C2-C 12 Alkyltrimethoxysilane groups, C2-C 12 Alkyltriethoxysilane groups, and C2-C 12For example, R1 to R3 can each include at least one selected from the group consisting of an ethyltrimethoxysilane group, a propyltrimethoxysilane group, a butyltrimethoxysilane group, a pentyltrimethoxysilane group, a hexyltrimethoxysilane group, a heptyltrimethoxysilane group, an octyltrimethoxysilane group, a nonyltrimethoxysilane group, a decyltrimethoxysilane group, an undecyltrimethoxysilane group, a dodecyltrimethoxysilane group, an ethyltriethoxysilane group, a propyltriethoxysilane group, a butyltriethoxysilane group, a pentyltriethoxysilane group, a hexyltriethoxysilane group, a heptyltriethoxysilane group, an octyltriethoxysilane group, a nonyltrimethoxysilane group, The silane group may include at least one selected from the group consisting of an ethyltriethoxysilane group, a decyltriethoxysilane group, an undecyltriethoxysilane group, a dodecyltriethoxysilane group, an ethyldimethoxyethoxysilane group, a propyldimethoxyethoxysilane group, a butyldimethoxyethoxysilane group, a pentyldimethoxyethoxysilane group, a hexyldimethoxyethoxysilane group, a heptyldimethoxyethoxysilane group, an octyldimethoxyethoxysilane group, a nonyldimethoxyethoxysilane group, a decyldimethoxyethoxysilane group, an undecyldimethoxyethoxysilane group, and a dodecyldimethoxyethoxysilane group.
[0052] According to one embodiment, R4 may have an H atom or a hydroxyl group at the end opposite to the portion linked to the methacryl group. According to one embodiment, for example, R4 may include at least one selected from the group consisting of H, a 2-hydroxyethyl group, a 3-hydroxypropyl group, and a 2-hydroxybutyl group.
[0053] According to an embodiment, the surface treatment agent may be a copolymer of two different methacrylate-based monomers, a copolymer of an acrylate-based monomer and a methacrylate-based monomer, or a copolymer of an epoxy-based monomer and a methacrylate-based monomer.
[0054] According to one embodiment, the properties of the surface treatment agent for a composition containing a compound represented by any one of the above [Chemical Formula 1] to [Chemical Formula 3] are determined by the ratio of m and n. According to one embodiment, m and n may have an integer ratio between 1:2 and 2:1. For example, m and n may have an integer ratio such as 1:1, 3:2, 2:3, 4:3, 5:3, 3:4, 5:4, or 7:4.
[0055] According to an embodiment, the surface treatment agent may be included in an amount of 10 to 30 parts by weight based on 100 parts by weight of the inorganic particles. If the surface treatment agent is included in an amount of less than 10 parts by weight based on 100 parts by weight of the inorganic particles, dispersibility may be reduced, and if the surface treatment agent is included in an amount of more than 30 parts by weight based on 100 parts by weight of the inorganic particles, curing may not be smooth during film production.
[0056] According to an embodiment, the surface treatment agent may further include at least one polymerization initiator selected from the group consisting of BPO (benzoyl peroxide), AIBN (azobis isobutyronitrile), and AIBA (2,2'-azobis(2-methylpropionamide) dihydrochloride). According to an embodiment, the polymerization initiator may include a paroxide-based compound, an azo compound, or both.
[0057] According to an embodiment, the polymerization initiator may be present in an amount of 0.1% by weight to 1% by weight in the surface treatment agent. When the polymerization initiator is present in an amount less than 0.1% by weight, copolymerization may proceed only partially, and when the polymerization initiator content exceeds 1% by weight, excess polymerization initiator may be distributed in the surface treatment agent and function as an impurity.
[0058] According to an embodiment, the light transmittance of the surface treatment agent may be 40% or more.
[0059] According to an embodiment, the light transmittance of the surface treatment agent may be 40% or more, 42% or more, 45% or more, or 50% or more.
[0060] According to one embodiment, the haze of the surface treatment agent may be less than 80%.
[0061] According to an embodiment, the haze of the surface treatment agent may be 80% or less, 70% or less, 60% or less, or 50% or less.
[0062] According to one embodiment, the composition may further include a dispersant containing at least one functional group selected from the group consisting of a carboxyl group, a phosphoric acid group, a phosphonic acid group, a sulfonic acid group, and a phenolic hydroxyl group. According to one embodiment, the dispersant may preferably contain a carboxyl group.
[0063] According to one embodiment, the dispersant can be commercially available. According to one embodiment, the dispersant can be a dispersant under the following trade names: DISPERBYK, DISPERBYK-101, DISPERBYK-102, DISPERBYK-103, DISPERBYK-106, DISPERBYK-107, DISPERBYK-108, DISPERBYK-109, DISPERBYK-110, DISPERBYK-111, DISPERBYK-112, DISPERBYK-115, DISPERBYK-116, DISPERBYK-118, DISPERBYK-130, DISPERBYK-140, DISPERBYK-142, DISPERBYK-145, DISPERBYK-160, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-164, DISPERBY K-165, DISPERBYK-166, DISPERBYK-167, DISPERBYK-168, DISPERBYK-169, DISPERBYK-170, DISPERBYK-171, DISPERBYK-174, DISPERBYK-176, DI SPERBYK-180, DISPERBYK-181, DISPERBYK-182, DISPERBYK-183, DISPERBYK-184, DISPERBYK-185, DISPERBYK-187, DISPERBYK-190, DISPERBYK- 191, DISPERBYK-192, DISPERBYK-193, DISPERBYK-194, DISPERBYK-2000, DISPERBYK-2001, DISPERBYK-2008, DISPERBYK-2009, DISPERBYK-2010 , DISPERBYK-2020, DISPERBYK-2025, DISPERBYK-2050, DISPERBYK-2070, DISPERBYK-2090, DISPERBYK-2091, DISPERBYK-2095, DISPERBYK-2096, DISPERBYK-2150, DISPERBYK-2151, DISPERBYK-2152, DISPERBYK-2155, DISPERBYK-2163, and DISPERBYK-2164.Further, according to one embodiment, the dispersant may include at least one selected from the group consisting of Antiterra-U, P104, Disperbyk 110, Disperbyk 130, Disperbyk 160, Disperbyk 170 Family, EFKA 776, EFKA 4050, EFKA 4063, EFKA 4051, Solsperse 24000, Solsperse 36600, Solsperse 32600, Solsperse 22000, and Solsperse 5000, in addition to the above trade names.
[0064] According to one embodiment, the dispersant may be included in an amount of 1 part by weight to 10 parts by weight based on 100 parts by weight of the composition. According to one embodiment, the dispersant may be included in an amount of 1 part by weight to 5 parts by weight, or 3 parts by weight to 7 parts by weight based on 100 parts by weight of the composition.
[0065] According to one embodiment, the composition further includes a dispersion solvent, and the dispersion solvent may include at least one selected from the group consisting of methyl ethyl ketone (MEK), ethanol, methanol, acetonitrile, toluene, tetrahydrofuran (THF), propylene glycol monomethyl ether acetate (PGMEA), and ethyl acetate.
[0066] According to an embodiment, the weight of the dispersion solvent may be equal to or greater than the weight of the surface-modified inorganic particles. According to an embodiment, the weight ratio of the surface-modified inorganic particles to the dispersion solvent may be 1:1 to 1:2.
[0067] According to one embodiment, the dispersion solvent may be present in the composition in an amount of 30% to 60% by weight. According to one embodiment, the dispersion solvent may be present in an amount of 30% by weight or more, 40% by weight or more, or 50% by weight or more, or 60% by weight or less, 50% by weight or less, 40% by weight or less, or in a range between any two values selected from the above-mentioned values.
[0068] According to an embodiment, the refractive index of the composition may be 1.50 to 1.80.
[0069] According to one embodiment, the composition is a high refractive index dispersion composition, having a refractive index of 1.50 or more, 1.55 or more, 1.60 or more, 1.65 or more, 1.70 or more, or 1.75 or more, or 1.80 or less, 1.75 or less, 1.70 or less, 1.65 or less, 1.60 or less, 1.55 or less, or any range between any two of the values mentioned above.
[0070] According to an embodiment, the viscosity of the composition may be 180 cPs to 20,000 cPs (based on 25° C.). According to an embodiment, the viscosity of the composition may be adjusted using a viscosity modifier such as MEK, toluene, or ethyl acetate, and according to an embodiment, the viscosity of the composition may be preferably 180 cPs to 10,000 cPs (based on 25° C.), and more preferably 180 cPs to 1,000 cPs (based on 25° C.).
[0071] According to one embodiment, the composition may have a haze of 15% or less.
[0072] According to one embodiment, the haze of the composition may be less than or equal to 15%, preferably less than or equal to 14%, and more preferably less than or equal to 6%.
[0073] The adhesive film according to an embodiment of the present invention may be manufactured using a composition according to an embodiment of the present invention. The adhesive film according to an embodiment of the present invention may be manufactured using a composition according to an embodiment of the present invention, which includes inorganic particles surface-modified by a surface treatment agent and an acrylic monomer, and the inorganic particles and the acrylic monomer have a weight ratio of 1:1 to 2:1.
[0074] According to an embodiment, the adhesive film may be an adhesive film such as an OCA film or a pressure sensitive adhesive (PSA) film, and may provide an adhesive film that is optically transparent while having flexibility.
[0075] The present invention will be described in further detail below with reference to examples and comparative examples.
[0076] However, the following examples are merely intended to illustrate the present invention, and the content of the present invention is not limited to the following examples.
[0077] 1. Manufacturing of surface treatment agents Example 1-1 As monomers, 3-methacryloxypropyltrimethoxysilane (MPTMS) and 2-hydroxyethyl methacrylate (2-HEMA) were mixed in a 1:1 weight ratio in a methyl ethyl ketone (MEK) solvent. As a polymerization initiator, 0.01 g of AIBN was added. At this time, the solvent was mixed in the same amount as the total weight of the monomers. After growing for 3 hours at 60°C under a nitrogen atmosphere, the mixture was stirred at room temperature for 12 hours to polymerize the monomers and obtain a polymer.
[0078] Comparative Example 1-1 A polymer was obtained in the same manner as in Example 1-1 above, except that 2-hydroxyethyl acrylate (2-HEA) was used instead of 2-HEMA.
[0079] Comparative Example 1-2 A polymer was obtained in the same manner as in Example 1-1 above, except that 2-hydroxybutyl acrylate (2-HBA) was used instead of 2-HEMA.
[0080] 2. Preparation of surface-treated inorganic particle dispersion Example 2-1 40 g of zirconia powder having an average particle size of 10 nm, 60 g of methyl ethyl ketone (MEK) as a dispersion solvent, and 20 parts by weight of the polymer of Example 1-1 as a surface treatment agent were added to 100 parts by weight of the zirconia powder, and dispersed for 3 hours to prepare an inorganic particle dispersion.
[0081] Example 2-2 An inorganic particle dispersion was prepared in the same manner as in Example 2-1, except that the amount of the surface treatment agent added was 30 parts by weight per 100 parts by weight of the zirconia powder.
[0082] Example 2-3 An inorganic particle dispersion was prepared in the same manner as in Example 2-1, except that the amount of the surface treatment agent added was 40 parts by weight per 100 parts by weight of the zirconia powder.
[0083] Comparative Example 2-1 An inorganic particle dispersion was prepared in the same manner as in Example 2-1, except that the polymer of Comparative Example 1-1 was added as the surface treatment agent.
[0084] Comparative Example 2-2 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-1, except that the amount of the surface treatment agent added was 30 parts by weight per 100 parts by weight of the zirconia powder.
[0085] Comparative Example 2-3 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-1, except that the amount of the surface treatment agent added was 40 parts by weight per 100 parts by weight of the zirconia powder.
[0086] Comparative Example 2-4 An inorganic particle dispersion was prepared in the same manner as in Example 2-1, except that the polymer of Comparative Example 1-2 was added as the surface treatment agent.
[0087] Comparative Example 2-5 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-4, except that the amount of the surface treatment agent added was 30 parts by weight per 100 parts by weight of the zirconia powder.
[0088] Comparative Example 2-6 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-4, except that the amount of the surface treatment agent added was 40 parts by weight per 100 parts by weight of the zirconia powder.
[0089] Comparative Example 2-7 40 g of zirconia powder having an average particle size of 10 nm, 60 g of methyl ethyl ketone (MEK) as a dispersion solvent, and 10 parts by weight of methacryloxypropyltrimethoxysilane as a surface treatment agent per 100 parts by weight of the zirconia powder were added and dispersed for 3 hours to prepare an inorganic particle dispersion.
[0090] Comparative Example 2-8 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-7, except that the amount of the surface treatment agent added was 15 parts by weight per 100 parts by weight of the zirconia powder.
[0091] Comparative Example 2-9 An inorganic particle dispersion was prepared in the same manner as in Comparative Example 2-7, except that the amount of the surface treatment agent added was 20 parts by weight per 100 parts by weight of the zirconia powder.
[0092] Experimental Example 1: Optical characteristics of inorganic particle dispersions In order to confirm the optical characteristics of the inorganic particle dispersions according to Examples 2-1 to 2-3 and Comparative Examples 2-1 to 2-9, the total light transmittance and haze were measured and are shown in Table 1 below.
[0093] [Table 1]
[0094] 3. Preparation of organic-inorganic hybrid composition Example 3-1 Based on the total composition, 50% by weight of methyl ethyl ketone (MEK) as a dispersion solvent, 40% by weight of zirconia powder with an average particle size of 10 nm, and 10% by weight of the polymer according to Example 1-1 as a surface treatment agent were mixed and stirred for 30 minutes. Then, in order to disperse the zirconia particles evenly, 200 parts by weight of zirconia beads (average particle size: 0.05 mm) were added based on 100 parts by weight of the above mixture, and the dispersion was dispersed for 3 hours using a paint shaker to recover the dispersion. Based on 50 parts by weight of the dispersion liquid produced, 45 parts by weight of butyl acrylate as an acrylic monomer and 5 parts by weight of a dispersant were added, and the dispersion solvent was removed under reduced pressure to produce a composition.
[0095] Example 3-2 A composition was prepared in the same manner as in Example 3-1 above, except that 2-ethylhexyl acrylate was added as the acrylic monomer.
[0096] Example 3-3 A composition was prepared in the same manner as in Example 3-1, except that isobornyl acrylate was added as the acrylic monomer.
[0097] Examples 3-4 A composition was prepared in the same manner as in Example 3-1 above, except that 4-acryloyl morpholine was added as the acrylic monomer.
[0098] Comparative Example 3-1 A composition was prepared in the same manner as in Example 3-1 above, except that methacryloxypropyltrimethoxysilane was added as the surface treatment agent.
[0099] Comparative Example 3-2 A composition was prepared in the same manner as in Comparative Example 3-1, except that 2-ethylhexyl acrylate was added as the acrylic monomer.
[0100] Comparative Example 3-3 A composition was prepared in the same manner as in Comparative Example 3-1, except that isobornyl acrylate was added as the acrylic monomer.
[0101] Comparative Example 3-4 A composition was prepared in the same manner as in Comparative Example 3-1, except that 4-acryloyl morpholine was added as the acrylic monomer.
[0102] Experimental Example 2: Properties of organic-inorganic hybrid composition In order to confirm the physical properties of the compositions according to Examples 3-1 to 3-4 and Comparative Examples 3-1 to 3-4, the refractive index, viscosity, and haze were measured and are shown in Table 2 below.
[0103] [Table 2]
[0104] Although the embodiments have been described above, those skilled in the art may apply various technical modifications and variations based on the above. For example, the described techniques may be performed in a different order than described, and / or the components of the described systems, structures, devices, circuits, etc. may be combined or combined in a different manner than described, or may be replaced or substituted with other components or equivalents, while still achieving appropriate results. Therefore, other implementations, other embodiments, and equivalents to the claims are also within the scope of the following claims.
Claims
1. A polymer formed by polymerizing only 3-methacryloxypropyltrimethoxysilane (MPTMS) and 2-hydroxyethyl methacrylate (2-HEMA) monomers in a 1:1 weight ratio. An inorganic particle surface treatment agent for organic-inorganic hybrid compositions.
2. 2. The inorganic particle surface treatment agent for an organic / inorganic hybrid composition according to claim 1, further comprising a polymerization initiator comprising at least one selected from the group consisting of BPO, AIBN, and AIBA.
3. The inorganic particle surface treatment agent for an organic / organic hybrid composition according to claim 2, wherein the polymerization initiator is present in an amount of 0.1% by weight to 1% by weight in the surface treatment agent.
4. 2. The inorganic particle surface treatment agent for an organic / organic hybrid composition according to claim 1, wherein the light transmittance of the surface treatment agent is 40% or more.
5. 2. The inorganic particle surface treatment agent for an organic / inorganic hybrid composition according to claim 1, wherein the haze of the surface treatment agent is 80% or less.
Citation Information
Patent Citations
Acrylic resin coated metallic pigment for water-based coating
JP1989259069A
Zinc oxide-based fine particle and its use
JP2003054947A
Resin for surface treatment, composite powder and application thereof
JP2015054820A
Modified copolymer, producting process and application thereof
KR1020170034116A
Resin-coated metallic pigment
WO2018100806A1